1992
DOI: 10.1111/j.1472-8206.1992.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Compared plasma and brain pharmacokinetics of clomipramine and its metabolite demethylclomipramine in two strains of mice (NMRI and CD1)

Abstract: The fate of clomipramine (CMI) and its main demethylated metabolite demethylclomipramine (DCMI) was studied in two strains of Swiss mice (NMRI and CD1) after intraperitoneal injection. A study of its distribution among various tissues showed that fixation was most marked in lungs, perirenal fat and kidneys, and only moderate in the brain. The pharmacokinetic parameters of both molecules were determined in brain tissue and plasma. Absorption was rapid (tmax CMI = 14 min), metabolism prompt (tmax DCMI = 17 or 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…8e ). Incredibly, the corresponding mean spinal cord levels were 28 and 1.5 μM; a similar high brain to plasma ratio of clomipramine was reported by Marty et al 21 in mice injected with a single 8 mg/kg clomipramine IP. There was a strong correlation of serum and spinal cord levels for both clomipramine and DMCL across mice (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…8e ). Incredibly, the corresponding mean spinal cord levels were 28 and 1.5 μM; a similar high brain to plasma ratio of clomipramine was reported by Marty et al 21 in mice injected with a single 8 mg/kg clomipramine IP. There was a strong correlation of serum and spinal cord levels for both clomipramine and DMCL across mice (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Of note, clomipramine levels after oral intake in humans have a wide range, leading to plasma concentrations of more than 600 nM in some individuals 18 , which is in the range of neuroprotection against iron in our in vitro experiments. The injection of 20 mg/kg IP in CD1 mice leads to peak plasma concentrations of 438 ng/ml (1.4 μM) with a half-life of 165 min 21 and in our experiments animals (sacrificed 1 h after the last injection) had mean serum clomipramine concentrations of 236.5 ng/ml (751 nM). These plasma levels are close to the ones measured in humans (average of 387 nM, and up to 600 nM 18 ), especially keeping in mind that plasma levels drop faster in mice due to the relatively bigger liver:body mass and that the half-life of clomipramine in humans is between 17.7 and 84 h 43 compared to about 2.5 h in mice.…”
Section: Discussionsupporting
confidence: 50%
“…Plasma levels of AM1 do not increase with repeated injections, while its short t , , (0.37 k 0.16 h) suggests a rapid absorption. This value agrees with that obtained after acute ip administration of AM1 (tmm = 0.37 h), trimipramine (t,, = 0.19 h) (Bougerolle et al, 1989) or clomipramine (t, , = 0.23 h) (Marty et al, 1992) in the same breed of mice. This stability of AM1 levels is probably due to a stimulation of AM1 metabolism that offsets the lengthening of the plasma elimination phase.…”
Section: Discussionsupporting
confidence: 89%
“…These drugs were chosen for their selectivity to their respective receptor subtypes (Artaiz et al, 2005;Han and Gu, 2006;Millan et al, 2001) and their behavioral effects in past work (Rasmussen and Newland, 2001;Reed and Newland, 2009), which demonstrated that the dose ranges used here captured changes in drug sensitivity following gestational MeHg exposure in rats. Previous work reported that damphetamine, desipramine, and clomipramine have half-lives of approximately 60 min (Fuller et al, 1972;Miller et al, 1971), 3-4 hours (Kozisek et al, 2007), and 54 min (Marty et al, 1992), respectively, in rats and mice. Drug injections occurred on Tuesdays and Fridays, saline vehicle was given on Thursdays, and Mondays and Wednesdays served as non-injection controls.…”
Section: Drugs and Drug Administrationmentioning
confidence: 98%